Con Academy - Schreiber, Joe, 1969- (Houghton Mifflin Harcourt, 2015)
Con man Will Shea may have met his match in scammer Andrea Dufresne as they make a high-stakes deal that will determine who gets to stay at Connaughton Academy, one of the most elite and privileged preparatory schools in the country, and who must leave.